Comparative Metabolic Analysis Reveals a Metabolic Switch in Mature, Hydrated, and Germinated Pollen in Arabidopsis thaliana - Wang, Jiang; Kambhampati, Shrikaar; Allen, Doug K.; Chen, Li-Qing (Frontiers in Plant Science, 2022)
Pollen germination is an essential process for pollen tube growth, pollination, and therefore seed production in flowering plants, and it requires energy either from remobilization of stored carbon sources, lipids and starches, or from secreted exudates from the stigma. Transcriptome analysis from in vitro pollen germination previously showed that 14 GO terms, including metabolism and energy, were overrepresented in Arabidopsis. However, little is understood about global changes in carbohydrate and energy-related metabolites during the transition from mature pollen grain to hydrated pollen, a prerequisite to pollen germination, in most plants, including Arabidopsis. In this study, we investigated differential metabolic pathway enrichment among mature, hydrated, and germinated pollen using an untargeted metabolomic approach. Integration of publicly available transcriptome data with metabolomic data generated as a part of this study revealed starch and sucrose metabolism increased significantly during pollen hydration and germination. We analyzed in detail alterations in central metabolism, focusing on soluble carbohydrates, non-esterified fatty acids, glycerophospholipids, and glycerolipids. We found that several metabolites, including palmitic acid, oleic acid, linolenic acid, quercetin, luteolin/kaempferol, and γ-aminobutyric acid (GABA), were elevated in hydrated pollen, suggesting a potential role in activating pollen tube emergence. The metabolite levels of mature, hydrated, and germinated pollen, presented in this work provide insights on the molecular basis of pollen germination.